Elastic waves propagation in an elastic layer with cubic anisotropic properties - K. B. Kazarian; M. V. Belubekian (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
This paper discusses a dinamic problem of an elastic wave propagation along an infinite layer with anisotropic properties of a single cubic crystal. The dispersion equation are deduced relating the coupled SP and P waves patterns phase velocities. In long a wave approximation the beam flexural and extensional vibration equations are obtained. In a short waves approximation the equation of the surface Releigh type waves is deduced. By means of the Kirchoff theory of plate the two dimensional dynamic equation of anisotropic plate is deduced. A comparition between the obtained results is carried out and effect of anisotropy is studied.
Keywords: Mechanics of particles and systems; Kinematics